Evaluation of the immunogenicity and impact on the latent HIV‐1 reservoir of a conserved region vaccine, MVA.HIVconsv, in antiretroviral therapy‐treated subjects. Issue 1 (19th May 2017) - Hancock, Gemma; Morón‐López, Sara; Kopycinski, Jakub; Puertas, Maria C.; Giannoulatou, Eleni; Rose, Annie; Salgado, Maria; Hayton, Emma‐Jo; Crook, Alison; Morgan, Catharine; Angus, Brian; Chen, Fabian; et al.
Abstract: Introduction : Vaccines may be key components of a curative strategy for HIV‐1. We investigated whether a novel immunogen, HIVconsv, designed to re‐direct T cell responses to conserved viral epitopes, could impact the HIV‐1 reservoir in chronic antiretroviral therapy (ART)‐treated subjects when delivered by modified vaccinia virus Ankara (MVA). Methods : Nineteen virologically suppressed individuals were randomized to receive vaccinations with MVA.HIVconsv (5.5 × 10 7 plaque‐forming units, pfu, n = 8; 2.2 × 10 8  pfu, n = 7) or placebo (n = 4) at 0, 4 and 12 weeks. Magnitude, breadth and antiviral function of vaccine‐induced T cells, cell‐associated HIV‐1 DNA in circulating CD4+ T cells and residual viremia in plasma were measured before and after vaccination. Results : 90% of subjects completed the vaccine regimen; there were no serious vaccine‐related adverse events. The magnitude of HIVconsv‐specific IFN‐ γ ‐secreting T cells was not significantly boosted in vaccinees when compared with placebos in ex vivo Elispot assays, due to greater than expected variation in HIV‐specific T cell responses in the latter during the observation period. Ex vivo CD8+ T cell viral inhibitory capacity was modest but significantly increased post‐vaccination with MVA.HIVconsv at the higher dose (p = 0.004) and was positively correlated with the frequency of HIVconsv‐specific CD8+ CD107+ IFN‐ α ± T cells (r = 0.57, p = 0.01). Total HIV‐1 DNA and residual viral load did not change significantly from baseline in any group. Conclusions : Homologous prime‐boost vaccination with MVA.HIVconsv was safe in HIV‐positive ART‐treated subjects but showed modest immunogenicity and did not significantly change the size of the viral reservoir. MVA.HIVconsv may be more effective when used in a heterologous prime‐boost vaccination regimen and when combined with a latency‐reversing agent. Clinical Trials Registration NCT01024842